Inflammasome in HIV infection: Lights and shadows. (February 2020) - Leal, Vinicius Nunes Cordeiro; Reis, Edione Cristina; Pontillo, Alessandra
Highlights: Inflammasome activation in HIV-1 contributes to the resistance against virus establishment. Constitutive activation in chronic infection has been associated to a worse prognosis. Use of inflammasome components as blood markers for differential prognosis and/or ART response. Inflammasome inhibitors as supportive therapy to prevents co-morbities. Rescue of inflammasome activation in HIV + patients could enhance response towards vaccination. Abstract: The importance of inflammasome, and related cytokines IL-1ß and IL-18, in host defense against pathogens is well documented, however, at the same time, dysregulation of inflammasome has been associated to multifactorial diseases characterized by chronic inflammation (i.e.: metabolic disorders, cardiovascular diseases, neurodegenerative diseases, autoimmunity, cancer). Inflammasome activation has been described in response to HIV-1 and possibly contributes to the resistance against virus establishment, however, on the other hand, when viral infection becomes chronic, independently from antiretroviral therapy, the increase constitutive activation of inflammasome has been eventually associated to a worse prognosis, raising the question about the role played by inflammasome and/or some specific receptors in this context. Due to the chance to imply targeted therapies that inhibit inflammasome activation and/or cytokines release, it will be important to define the impact of the complex in the pathogenesis of HIV. The purpose of this review is to depict the double-faced inflammasome role in HIV-1 infection, trying to unveil whether besides its role in first line defense against the virus, it exerts a harmful effect during the chronic phase of infection.